Demonstration of a Functionally Active tPA-Like Plasminogen Activator in Human Platelets - Wang, D L; Pan, Y T; Wang, J J; Cheng, C H; Liu, C Y (Thrombosis and Haemostasis, 1994)
The mechanism of platelet-enhanced fibrinolysis is unclear. We therefore investigated the fibrinolytic activity of human platelets and demonstrated that they contain a tissue plasminogen activator (tPA)- like plasminogen activator, abbreviated as tPA-like-PA. This activator was detected by ELISA in platelet incubation medium and in platelet Triton extracts. Plasminogen activation assays showed that this tPA- like-PA could induce plasminogen activation to form plasmin. Western blots of Triton extracts incubated with anti-tPA antibody demonstrated a major 64-kD protein band, compared to a 70-kD band for standard single chain tPA, plus a minor 118-kD band corresponding to a complex of tPA-like-PA and plasminogen activator inhibitor (PAI-1). Western blots of Triton extracts incubated with anti-PAI-1 antibody produced an approximately similar high-molecular-weight (118 kD) protein band. Fibrin zymographic analysis of affinity-purified tPA-like- PA demonstrated a major and a minor fibrin lysis zone, which approximately corresponded to the tPA-like-PA and its complex with PAI-1 observed by Western blots. Immunogold labelling and electron microscopy demonstrated that platelet activator, either as the free form or co-localized with PAI-1, was present in granules and in channels of the open canalicular system. We conclude that platelets contain a functionally active tPA-like-PA, whose low fibrinolytic activity might be due to its readily forming a complex with PAI-1. This functionally active tPA-like-PA might contribute to the enhanced fibrinolytic activity of platelets observed in platelet-rich thrombi.